Effects of Lateral Window Position and Wind Direction on Wind-Driven Natural Cross Ventilation of a Building: A Computational Approach. (11th March 2014) - Bangalee, M. Z. I.; Miau, J. J.; Lin, S. Y.; Ferdows, M.
Abstract : Energy is saved when an effective natural ventilation system can provide comfort air to the occupants in a building by replacing a mechanical ventilation system. It also minimizes the risk of the environmental pollution and the global warming. A one story, full scale building was considered to carry out a comparative study of three different cases of wind-driven natural (WDN) cross ventilation with the help of computational fluid dynamics (CFD). In each case, the location of window was changed in lateral direction to predict the probable position for optimum ventilation performance and the angle of wind was varied to check the sensitivity of the wind direction on the flow field. After validating the current methodology through two satisfactory comparisons with the experimental investigations, the governing equations subjected to the corresponding boundary conditions were solved using commercial software and then the results were analyzed. A better location for the windows in each case was proposed. The ventilation purpose was served quite well even if the wind angle was changed in a moderate range from the original design. Furthermore, the velocity components, ventilation rate, surface pressure, ventilation time, and so forth in each case were investigated and compared extensively with those in other cases.